Examining the correlation between hemoglobin-red blood cell distribution width ratio and hospital mortality among patients with spontaneous intracerebral hemorrhage - Yu-Hua Huang; Tsung-Han Lee; Yu-Ming Chang (World Neurosurgery: X)
Objective: Spontaneous intracerebral hemorrhage (ICH) is a public health concern due to its high mortality rate. Although the hemoglobin to red blood cell distribution width ratio (Hb-RDW ratio) has been recognized as a prognostic indicator in numerous malignant conditions, its correlation with cerebrovascular event outcomes remains unclear. This study sets out to explore the association between the Hb-RDW ratio and hospital mortality after spontaneous ICH. Methods: We conducted a retrospective analysis of 201 patients, gathering information on Glasgow Coma Score (GCS), existing medical conditions, and laboratory results. The Hb-RDW ratio was calculated using the formula: Hb (gm/dl)/RDW (%). The primary endpoint was hospital mortality. We performed a multivariable logistic regression analysis to pinpoint independent predictors of hospital mortality. Results: The results disclosed a substantial inverse relationship between the Hb-RDW ratio and hospital mortality (OR: 0.06, 95 % CI: 0.004–0.90, p = 0.04). For every unit decrease in the Hb-RDW ratio, a 94 % increase in the risk of mortality was observed. A receiver operating characteristic curve analysis was performed, and the area under the curve for the Hb-RDW ratio was 0.633 (p = 0.01). Admission GCS was also an independent predictor of mortality (OR: 17.86, 95 % CI: 2.60–122.64, p < 0.01). Conclusions: The Hb-RDW ratio serves as a significant predictor of hospital mortality in patients with spontaneous ICH. Lower Hb-RDW ratio values corresponded to a heightened mortality risk, underscoring the potential usefulness of this composite index in guiding clinical decisions and risk stratification.